2011
DOI: 10.1152/jn.00236.2011
|View full text |Cite
|
Sign up to set email alerts
|

Differences in intersaccadic adaptation transfer between inward and outward adaptation

Abstract: Schnier F, Lappe M. Differences in intersaccadic adaptation transfer between inward and outward adaptation. J Neurophysiol 106: 1399 -1410. First published June 15, 2011 doi:10.1152/jn.00236.2011.-Saccadic adaptation is a mechanism to increase or decrease the amplitude gain of subsequent saccades, if a saccade is not on target. Recent research has shown that the mechanism of gain increasing, or outward adaptation, and the mechanism of gain decreasing, or inward adaptation, rely on partly different processes. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

6
13
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 54 publications
6
13
0
Order By: Relevance
“…Zimmermann and Lappe (2010) showed that visual localization of eccentric targets during fixation was much more susceptible to saccadic adaptation for outward than for inward adaptation. These results, together with those of Schnier and Lappe (2011) and Ethier et al (2008), suggest that there is a stronger modulation of target localization stages after outward than that after inward adaptation of reactive saccades. In this view, target localization stages, located before the sensorimotor transformation, are especially used in the execution of overlap and scanning saccades, leading to a higher amount of transfer to these latter saccade types dependent on whether target localization stages are modulated by saccadic adaptation.…”
supporting
confidence: 63%
See 4 more Smart Citations
“…Zimmermann and Lappe (2010) showed that visual localization of eccentric targets during fixation was much more susceptible to saccadic adaptation for outward than for inward adaptation. These results, together with those of Schnier and Lappe (2011) and Ethier et al (2008), suggest that there is a stronger modulation of target localization stages after outward than that after inward adaptation of reactive saccades. In this view, target localization stages, located before the sensorimotor transformation, are especially used in the execution of overlap and scanning saccades, leading to a higher amount of transfer to these latter saccade types dependent on whether target localization stages are modulated by saccadic adaptation.…”
supporting
confidence: 63%
“…Transfer from reactive saccades to overlap and scanning saccades is significantly stronger after outward adaptation than that after inward adaptation (Schnier and Lappe 2011). Such a transfer difference was not found for the gap and the memoryguided saccade type, suggesting that the amount by which gain transfer differed between inward and outward adaptation for scanning and overlap saccades seems to be essentially related to the presentation duration of the saccade target.…”
mentioning
confidence: 76%
See 3 more Smart Citations